Consumer Protection for Goods That Do Not Match Advertisements in E-Commerce Transactions - Farid Mujahidin; Muhamad Fatrus Abdurahman; Dafa Hidayatullah; Dudung Hidayat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Consumer protection laws, the responsibilities of business actors, and the actions of E-Commerce companies are very important to protect the rights of consumers when shopping on E-Commerce. This is necessary considering the vulnerable position of consumers who are very weak so that they become victims of the goods they receive. This research aims to explain who is responsible for the dispute between business actors and consumers if the goods received by consumers are not in accordance with those advertised by business actors in order to protect consumer rights. The method of approach used in this research is Juridical-Empirical by conducting research sourced from secondary and primary data. Secondary data such as documents, reports, books, articles, laws and regulations, court decisions, and others. While the primary data in this study are the results of interviews. In this case, the responsible party is the business actor who must replace the goods they send to consumers or return the funds that consumers have spent on these goods. In addition to the responsible business actors, E-Commerce also does not escape its obligations as a place of meeting between business actors and consumers. So that E-Commerce must carefully face the problems that occur between business actors and consumers, especially facing Business Actors who make advertisements that do not match the condition of the original goods.